Humoral Response to SARS-CoV-2 Antigen in Patients Treated with Monoclonal Anti-CD20 Antibodies: It Is Not All about B Cell Recovery - Julia Feige; Klaus Berek; Michael Seiberl; Patrick Hilpold; Wolfgang Hitzl; Franziska Di Pauli; Harald Hegen; Florian Deisenhammer; Eugen Trinka; Andrea Harrer; Peter Wipfler; Tobias Moser (MDPI AG, 2022)
Anti-CD20 therapies decrease the humoral response to SARS-CoV-2 immunization. We aimed to determine the extent of the humoral response to SARS-CoV-2 antigens in correlation with peripheral B-cell dynamics among patients with central nervous system inflammatory disorders treated with anti-CD20 medications. We retrospectively included patients receiving anti-CD20 therapy after antigen contact who were divided into responders (>7 binding antibody units (BAU)/mL) and non-responders (<7 BAU/mL). In participants with first antigen contact prior to therapy, we investigated the recall response elicited once under treatment. We included 80 patients (responders n = 34, non-responders n = 37, recall cohort n = 9). The B-cell counts among responders were significantly higher compared to non-responders (mean 1012 cells/µL ± SD 105 vs. mean 17 cells/µL ± SD 47; p < 0.001). Despite very low B-cell counts (mean 9 cells/µL ± SD 20), humoral response was preserved among the recall cohort (mean 1653 BAU/mL ± SD 2250.1) and did not differ significantly from responders (mean 735 BAU/mL ± SD 1529.9; p = 0.14). Our data suggest that peripheral B cells are required to generate antibodies to neo-antigens but not for a recall response during anti-CD20 therapy. Evaluation of B-cell counts and pre-existing SARS-CoV-2 antibodies might serve as biomarkers for estimating the immune competence to mount a humoral response to SARS-CoV-2 antigens.